Trade and the Spatial Distribution of Transport Infrastructure - Gabriel J. Felbermayr; Alexander Tarasov (Center for Economic Studies and ifo Institute (CESifo), 2015)
The distribution of transport infrastructure across space is the outcome of deliberate government planning that reflects a desire to unlock the welfare gains from regional economic integration. Yet, despite being one of the oldest government activities, the economic forces shaping the endogenous emergence of infrastructure have not been rigorously studied. This paper provides a stylized analytical framework of open economies in which planners decide non-cooperatively on transport infrastructure investments across continuous space. Allowing for intra- and international trade, the resulting equilibrium investment schedule features underinvestment that turns out particularly severe in border regions and that is amplified by the presence of discrete border costs. In European data, the mechanism explains about a fifth of the border effect identified in a conventionally specified gravity regression. The framework sheds light on the welfare costs of second best investment schedules, on the effects of intercontinental trade or of privatized infrastructure provision.
Keywords: F11; R42; R13; 330; economic geography; international trade; infrastructure investment; border effect puzzle